Ragam Bahan Untuk Pembuatan Pakan Khusus Yang Diberikan Kepada Pasangan Kerbau Sumbawa Karapan Sebelum Bertanding (Studi Di Kecamatan Empang Kabupaten Sumbawa): Variety Of Ingredients For Manufacturing Special Feeds Given To Couples Sumbawa Buffalo Racing Before The Competition (Study In Empang District, Sumbawa Regency) - Syamsul Hidayat Dilaga; Sofyan Sofyan; Suhubdy Suhubdy; Muhammad Amin; Oscar Yanuarianto (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
A survey was conducted in Empang sub-district, which has many Sumbawa buffalo racing enthusiasts. Before the animals are competed, are they given special feed/herbs? What are their chances of winning? This is what the research will seek to answer, as there is no written information on this subject. The survey found that all farmers give special feed/herbs to their raced sumbawa buffaloes, but the ingredients/recipes differ, ranging from the most complete recipe consisting of 17 ingredients, the medium recipe consisting of 12 ingredients, and the minimalist recipe consisting of 9 ingredients.  All of them have won. The complete recipe won first place (43 pairs of buffalo), the medium recipe won second place (48 pairs of buffalo), and the minimalist recipe (29 pairs of buffalo) won third place.